Unlocking the power of precision medicine: exploring the role of biomarkers in cancer management - Dipak D. Gadade; Hariom Jha; Chetan Kumar; Farzan Khan (SpringerOpen, 2024)
Abstract Background Personalized or Precision medicine (PM) is a promising approach for the cancer treatment that tailors treatment to a patient's characteristics. Biomarkers are crucial for identifying the patients who are expected to derive greatest advantage from targeted therapy. Main body Here, various biomarkers, including genetic, epigenetic, protein, and metabolites, and their clinical significance, are discussed. The review provides insights into the use of biomarkers and their clinical significance in cancer treatment. There are several hurdles in use of PM in oncology, such as the complexity of tumor biology and heterogeneity, limited availability of biomarkers, high cost of targeted therapies, resistance to targeted therapies, and ethical and social issues. Conclusion The biomarkers play a crucial diagnostic role in the treatment of cancer. The review also acknowledges the challenges and limitations of personalized medicine which, if resolved, can be helpful in the management of cancer.